In vivo Infection Dynamics and Human Adaptive Changes of SIVsm-Derived Viral Siblings SIVmac239, SIVB670, and SIVhu in Humanized Mice as a Paralog of HIV-2 Genesis - Curlin, James Z.; Schmitt, Kimberly; Remling-Mulder, Leila; Moriarty, Ryan V.; Baczenas, John J.; Goff, Kelly; O'Connor, Shelby; Stenglein, Mark; Marx, Preston A.; Akkina, Ramesh (Frontiers in Virology, 2021)
Simian immunodeficiency virus native to sooty mangabeys (SIVsm) is believed to have given rise to HIV-2 through cross-species transmission and evolution in the human. SIVmac239 and SIVB670, pathogenic to macaques, and SIVhu, isolated from an accidental human infection, also have origins in SIVsm. With their common ancestral lineage as that of HIV-2 from the progenitor SIVsm, but with different passage history in different hosts, they provide a unique opportunity to evaluate cross-species transmission to a new host and their adaptation/evolution both in terms of potential genetic and phenotypic changes. Using humanized mice with a transplanted human system, we evaluated in vivo replication kinetics, CD4+ T cell dynamics and genetic adaptive changes during serial passage with a goal to understand their evolution under human selective immune pressure. All the three viruses readily infected hu-mice causing chronic viremia. While SIVmac and SIVB670 caused CD4+ T cell depletion during sequential passaging, SIVhu with a deletion in nef gene was found to be less pathogenic. Deep sequencing of the genomes of these viruses isolated at different times revealed numerous adaptive mutations of significance that increased in frequency during sequential passages. The ability of these viruses to infect and replicate in humanized mice provides a new small animal model to study SIVs in a vivo context in addition to more expensive macaques. Since SIVmac and related viruses have been indispensable in many areas of HIV pathogenesis, therapeutics and cure research, availability of this small animal hu-mouse model that is susceptible to both SIV and HIV viruses is likely to open novel avenues of investigation for comparative studies using the same host.